Surviving and thriving as a safe effective board member : the essential facts you need to know before, during and after joining a community board. (Our Community Pty Ltd, 2003)
This important book concentrates on the need for community directors to understand what it is that is actually required of them in terms of the issues that one must be aware of before joining a board, the responsibilities, legal requirements and duties while on the board, and what must be done before leaving a board.